Building and Standardizing a Test to Measure Motor Reaction Time Using an Apparatus with a Visual Stimulus for Physical Education and Sports Science College Students - Kadhim, Mohammed; Ali, Saqar (Journal of Physical Education, 2015)
The study consisted of five chapters. Chapter One included the introduction and the importance of the study which is summed up by introducing an apparatus with a visual stimulus designed by the researcher to test and measure the variable of motor reaction time by giving the order or the signal to take the test and measure the duration of the test electronically and accurately. The aims of the study: 1. Designing an apparatus with a visual stimulus to measure the time of motor reaction for the students of Physical Education and Sports Science College-Baghdad University. 2. Building and standardizing a test using an apparatuses with a visual stimulus to measure the time of motor reaction for the students of Physical Education and Sports Science College-Baghdad University. Chapter Two included some topics that are directly related to the variables of the study. Chapter Three tackled the method of the study and its procedures. The researcher has adopted the descriptive method using survey approach because it is the best to solve the problem of the study. The original community of the study has been intentionally selected to represent (701) students of Physical Education and Sports Sciences College- Baghdad University for the academic year 2014-2015. Totally, (200) students were randomly selected (50) students of each stage to represent the subject of the study. They have rated (28.54%) percent of the total number. In Chapter Four however the results of the test designed by the researcher were displayed and percentages of subjects’ levels of performance were extracted